Low levels of awareness and motivation towards cancer prevention amongst the general public in Sweden: a cross-sectional study focusing on the European Code Against Cancer - Cecilia Hultstrand; Ellen Brynskog; Andreas Karlsson Rosenblad; Anna-Lena Sunesson; Thomas Björk-Eriksson; Lena Sharp (BMC Public Health)
Abstract Background The European Code Against Cancer (ECAC) aims to increase the awareness of modifiable cancer risk factors among the general public. A goal set by the European Commission was that 80% of European citizens should be aware of this code by 2025. This study aims to examine the awareness and attitudes towards the ECAC among the general public in Sweden. Methods A randomly selected sample of 1520 Swedes (18–84 years old) were recruited from a survey panel and invited to respond to an online study-specific questionnaire. The questionnaire included general questions regarding cancer prevention, as well as awareness and attitudes specific to the ECAC. Data were analysed univariately and with adjusted logistic regression, using post-stratification weights based on gender, age, education, and expressed political party orientation. Results In total, 3.7% of the respondents had heard about the ECAC before taking this survey. Respondents with a college/university education were more likely to have heard about the ECAC (odds ratio [OR] 2.23; 95% confidence interval [CI] 1.23–4.06). Males (OR 0.56; 95% CI 0.32–0.99), and those living alone (OR 0.47; 95% CI 0.23–0.95) were less likely to have heard about the ECAC. In total, 60.6% of the respondents agreed with the ECAC recommendations, while 27.4% reported that their motivation to improve their lifestyle increased after reading the ECAC. Conclusions Awareness of the ECAC among the general public in Sweden is very low. Still, a majority seem to agree with its recommendations. The results also indicate that the ECAC motivates some, but far from all, to improve their lifestyle habits to reduce their cancer risk. Consequently, further research is warranted on how the ECAC best could and should be used in order to improve cancer prevention awareness and motivation.